2019
DOI: 10.1111/obr.12975
|View full text |Cite
|
Sign up to set email alerts
|

Histidine‐containing dipeptides reduce central obesity and improve glycaemic outcomes: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Supplementation with histidine-containing dipeptides has been shown to improve obesity and glycaemic outcomes in animal and human studies. We conducted a systematic review and meta-analysis of randomized controlled trials to examine these effects. Electronic databases were searched investigating the effects of histidinecontaining dipeptides supplementation on anthropometric and glycaemic outcomes.Meta-analyses were performed using random-effects models to calculate the weighted mean difference and 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 63 publications
3
32
1
Order By: Relevance
“…Indeed, oral carnosine supplementation ameliorates DN [ 4 ] and diabetic retinopathy (DR) [ 5 ] in Type 2 and Type 1 diabetic models while overexpression of CN-1 aggravates diabetes [ 4 ]. Although the number of studies performed in humans is limited, it seems that HCD also improves obesity and glycemic outcomes in men [ 6 , 7 ]. Yet, in humans, the protective effect of HCD is hampered by rapid hydrolysis of HCD because of high CN-1 activities and concentrations in human serum.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, oral carnosine supplementation ameliorates DN [ 4 ] and diabetic retinopathy (DR) [ 5 ] in Type 2 and Type 1 diabetic models while overexpression of CN-1 aggravates diabetes [ 4 ]. Although the number of studies performed in humans is limited, it seems that HCD also improves obesity and glycemic outcomes in men [ 6 , 7 ]. Yet, in humans, the protective effect of HCD is hampered by rapid hydrolysis of HCD because of high CN-1 activities and concentrations in human serum.…”
Section: Introductionmentioning
confidence: 99%
“…However, the published review outcomes are stated as "measurement of any anthropometric or glycemic outcomes". 1 It is not clear why the authors deviated from their pre-planned methods. Selective outcome reporting is a methodological concern, and it can introduce bias into the analyses based on results that return significant findings.…”
Section: Cant (See Our Reanalysis Of Figures 3-5 In the Supporting Inmentioning
confidence: 99%
“…We read with interest the recent paper by Menon et al in Obesity Reviews, which stated its aim as being to assess the effect of histidinecontaining dipeptides (HCDs) on anthropometric and glycaemic outcomes. 1 The study concluded that "HCD supplementation improved waist circumference, fasting glucose, and HbA1c"; whilst this is an interesting conclusion and highlights a further potential physiological role for HCDs, we have some questions over the ability to make such a conclusion from the approach taken.…”
mentioning
confidence: 97%
“…There have been a number of studies in which dietary supplementation with carnosine has been explored. Beneficial effects have been observed in schizophrenics [ 45 ], Gulf War veterans [ 49 ], obese humans [ 50 ], diabetics [ 51 ], elderly human verbal memory [ 52 ], autistic children [ 53 , 54 ] and patients with chronic heart failure [ 55 ]. Unfortunately, a major problem with oral administration of carnosine is the presence of carnosinase in serum which will destroy the peptide; indeed high carnosinase activity can limit the efficacy of orally administered carnosine towards chronic kidney disease [ 56 ].…”
Section: Carnosine As a Possible Senotherapeuticmentioning
confidence: 99%